MULTICULTURAL SCHOOL MANAGEMENT IN CULTURE DEVELOPMENT RELIGIOUS INCLUSIVE AT SMK BAKTI KARYA PARIGI WEST JAVA - Zainun Wafiqatun Niam; Daimah Daimah (International Conference on Social and Islamic Studies, 2021)
Education as a sub-culture of society should be able to contribute to building harmony abovedifferences, especially religious differences. One of the efforts that can be taken in this regard isthe practice of multicultural school management. The existence of multicultural schoolmanagement shows that schools officially recognize diversity through policies in order toorganize and accept this diversity. Through the implementation of multicultural schoolmanagement at SMK Bakti Karya Parigi Pangandaran, West Java, it is hoped that education willbe able to contribute to developing religious inclusivism in social life. The method used in thisresearch is field research using a qualitative approach. The main subjects in this study were theprincipal and manager of SMK Bakti Karya Parigi Pangandaran, West Java. This research can beused as a material object is SMK Bakti Karya Parigi and the formal object is MulticulturalSchool Management in the Development of Inclusive Religious Culture. Data collectiontechniques used participatory observation, interviews, documentation and data triangulation. Meanwhile, the data analysis used Spradley model data analysis technique with domain,taxonomy, componential, cultural and triangulation analysis. The results show that theimplementation of multicultural school management at SMK Bakti Karya has included allmanagement functions, from planning, organizing, implementing, and supervising schools andone of the results of the practice of multicultural school management is the development of areligiously inclusive culture in the school environment and the surrounding community. This can be proven by the school's ability to accommodate differences, especially religiousdifferences in the school environment to reach school goals together.